Major sites of cancer occurrence among men and women in Gandhinagar District, India - Parimal J Jivarajani; Himanshu V Patel; Rupal R Mecwan; Jayesh B Solanki; Vishruti B Pandya (Wolters Kluwer Medknow Publications, 2015)
Background: This study examines major cancer sites among the population of Gandhinagar district, India during the year 2009-2011. Objective: To study leading cancer incidents and mortality and their age distribution in both sexes in Gandhinagar district. Materials and Methods: Primary data were collected from various sources and entered in computer and analyzed. Quality checks were done, and duplicate cases were eliminated. For mortality data, death registration units were contacted. Results: Total 2360 incident cases (1374 males and 986 females) and 736 mortality cases (464 males and 272 females) were recorded during the year 2009-2011 in Gandhinagar district. Among males, the leadings sites were mouth, tongue, lung, esophagus, hypopharynx, and larynx, whereas in females they were breast, cervix, ovary, mouth, tongue and myeloid leukemia. Majority of cases were found in the age group of 35-64 years and the proportion in male and female in this age group was 62.51% and 71.05%, respectively. Conclusion: The study helps to understand the possible cancer patterns in Gandhinagar district. Foremost causes of cancer in leading sites in males were tobacco related, and the proportion of cancers associated with tobacco was 53% in our study. It highlights the possibility of easy and early detection of cancers, especially by oral cancer screening in the population. Further, the findings highlight the need of cancer cervix and breast screening among the women at regular intervals through camp approach in the community, as these are the most common sites (40% of female cancers).